(The struggle for) refugee integration into the labour market: evidence from Europe - Fasani, Francesco; Frattini, Tommaso; Minale, Luigi (Bonn, 2018)
"In this paper, we use repeated cross-sectional survey data to study the labour market performance of refugees across several EU countries and over time. In the first part, we document that labour market outcomes for refugees are consistently worse than those for other comparable migrants. The gap remains sizeable even after controlling for individual characteristics as well as for unobservables using a rich set of fixed effects and interactions between area of origin, entry cohort and destination country. Refugees are 11.6 percent less likely to have a job and 22.1 percent more likely to be unemployed than migrants with similar characteristics. Moreover, their income, occupational quality and labour market participation are also relatively weaker. This gap persists until about 10 years after immigration. In the second part, we assess the role of asylum policies in explaining the observed refugee gap. We conduct a difference-in-differences analysis that exploits the differential timing of dispersal policy enactment across European countries: we show that refugee cohorts exposed to these polices have persistently worse labour market outcomes. Further, we find that entry cohorts admitted when refugee status recognition rates are relatively high integrate better into the host country labour market."